Request Strategies as Seen in the Movie Silver Linings Playbook - Falminda Rahmadiyanti Tambulana; Adi Sutrisno (Lexicon, 2020)
This research aimed to investigate the types of request strategies used by the characters in the movie Silver Linings Playbook (2012). It also identified the types of request goals made by the characters. The data were taken from dialogues in the movie, which contained request utterances. The data were then classified into nine strategy types of request according to Blum-Kulka and Olshtain (1984), followed by the classification of the data into four types of request goals according to the theory proposed by Blum-Kulka et al. (1985, as cited in Forgas, 1985, p. 118). The result showed that 202 request strategies were made by the characters. The most frequently used request strategy found in the movie was a direct request, which was mood derivable with 111 occurrences (54.9%). Meanwhile, for request goals, requests for action was the most frequently implored type by the characters, and it was dominated by mood derivable strategy with 103 occurrences (64.8%).